Reservoir Quality of the Triassic Snadd and Kobbe Formations in the Barents Sea - Gyenis, Tímea (2016)
Geologically, the Barents Sea with deep sedimentary basins, highs and platforms is a complex mosaic and formed as a result of different geologic and tectonic processes with complex geological history. The history of the Barents Sea started 400 million years ago and continued until continental crustal separation which led to develop the Atlantic and Arctic oceans. The Barents Sea is a challenging area for hydrocarbon exploration. The reservoirs are mainly Jurassic age sandstones. The predominance of gas over oil and leakage of hydrocarbons from the traps are source of the problems in the exploration. These problems are related to Cenozoic erosion and uplift of the Barents Sea area. The Triassic Snadd and Kobbe Formations located on the southern part of the Bjarmeland Platform in SW Barents Sea are the focus of this study. The Snadd and Kobbe reservoirs are several meters thick and has good (Snadd) and poor (Kobbe) reservoir quality. Sedimentological, petrographic and petrophysical analysis have been done providing core material, thin sections and well log dataset from well 7222/11-1 (Caurus). The main objective was to characterize reservoir properties within these formations. The depositional environment for both sandstones has been interpreted as tide-dominated delta system with several subenvironments. The Kobbe Formation deposited during low energy conditions such as muddy shelf, inter- to supratidal flats, while the Snadd sandstones have been interpreted as tidal channel sandstone bodies. The Snadd Formation is well-sorted very fine- to fine-grained sandstone with moderate clay and carbonate content and the Kobbe Formation is moderately-sorted, very fine-grained sandstone with high clay content. Both formations are lithic arenites. Compositionally there is no significant difference between the two formations and the source area has been interpreted as eastern source area (Uralides) for both Kobbe and Snadd Formations. The main diagenetic minerals in both Kobbe and Snadd Formations are chlorite coating, pore-filling chlorite, kaolinite, pyrite, carbonate and quartz cement. The chlorite coating is well-developed in the Snadd Formation and preventing quartz cementation, while in the Kobbe Formation the chlorite coating is non-continuous hence there are slightly more quartz overgrowths present. The chlorite may have formed when fresh river water brought iron-rich material into seawater and the clay particles flocculated in the fluvial-marine mixing zone. The source of pore-filling authigenic kaolinite is mainly the dissolved mica and feldspar grains. Kaolinite is generally associated with pore-filling fibrous chlorite and microporosity. Two types of siderite cements are present in the formations, rhombic shape siderite, which sometimes appears within expanded mica grains, and small spherulitic patches of siderite within the samples. The iron-rich material brought by river water could be a source of siderite. The source of calcite cement is mainly the carbonate fossils are present in the samples. The pyrite is present both as framboidal and blocky crystals in the sandstones. The Snadd Formation sandstones show good porosity (4-28.2%) due less effect of mechanical compaction and chlorite coating preserves porosity. The permeability is mostly good but where the pore-filling authigenic clay minerals are present in the pore space the permeability shows low value. The Snadd Formation has been interpreted to have good reservoir quality. The Kobbe Formation sandstones has very fine grain size, high clay and matrix content, therefore mechanical compaction affects more in the Kobbe sandstones, resulting low porosity and permeability values. The Kobbe Formation has been interpreted to have poor reservoir quality. The presence of quartz overgrowths indicate that the two formations have been buried at deeper depth than at present. The absence of illite suggests that the temperature did not exceed 130 °C before uplift. The maximum uplift has been estimated 1.3-1.6 km in well 7222/11-1. The Kobbe Formation was more deeply buried (3.5-3.8 km) than the Snadd Formation (2.6-2.9 km).